Optical 1-soliton solutions of Triki-Biswas equation by the First Integral Method and the sine-cosine Method - Subhaschandra Singh, S. (International Journal of Physical Research, 2021)
In this paper, the First Integral Method and the Sine-Cosine Method are being used in constructing optical 1-soliton solutions of Triki-Biswas Equation that plays a vital role in the study of soliton dynamics of sub-pico-second optical pulses in mono-mode optical fibers with non-Kerr law nonlinearity and subsequently some soliton and non-soliton solutions are formally obtained.Â Â